La figura di Niobe silente in Eschilo: la testimonianza del fr. 154a Radt (Gilgameš, 2019)
In Aeschylean theatre silence reflects the feelings of the characters: anger, sadness, pain are often represented through non-verbal communication. Niobe, as a mater dolorosa, is the best example of an Aeschylean silent character: secluded in her mourning, she decides not to speak and refuses to communicate with the other characters; in this way she lives in her solitude, while she sits on her children’s grave for three days. The fr. 154a Radt testifies this position on the stage and validates the information we were given by Ar. Ra. 911-913; T 1.20 Radt; Σ [BCDMNPPdVWXY] ad A. Pr. 436a; Σ [B*NcP*SjWXcYa] ad A. Pr. 437a.